Liver transplantation combined with tyrosine kinase inhibitors for the treatment of hepatic metastatic giant gastrointestinal stromal tumors: A case report and literature review - Qian, Jun Lin; Hu, Ze Min; He, Kun; He, Yong Zhu (Frontiers in Gastroenterology, 2022)
Abstract Background: Surgical resection combined with oral tyrosine kinase inhibitors(TKI) is the most effective treatment for gastrointestinal stromal tumor(GIST) liver metastases. Liver transplantation (LT) is the last resort for the treatment of terminal liver malignancy. Whether it can be a potential treatment option for liver metastases from unresectable GIST is worth exploring. Case presentation: We report a 38-year-old woman who underwent jejunal stromal tumor resection and TKI(imatinib) therapy 15 years ago for jejunal stromal tumor liver metastases. During the period from 2015 to 2018, the liver metastases continued to grow after the patient stopped taking imatinib voluntarily, and the patient subsequently underwent multiple interventional surgeries and drug treatments, which were still poorly curative. The tumor was deemed unresectable because it filled the entire liver, and the patient subsequently underwent LT and was treated with imatinib post-operatively, which resulted in no recurrence of the tumor within 18 months of follow-up. Literature review: There are few reports in the literature on LT for the treatment of liver metastases from GIST. A systematic review and summary of the current literature by literature search revealed that LT as a last resort for metastatic GIST of the liver remains a major challenge. Conclusions: LT combined with TKI-targeted therapy is a potential therapy worth exploring for patients with unresectable metastatic GIST.